The Electromagnetic Calorimeter for the T2K Near Detector ND280 - Allan, D; Andreopoulos, C; Angelsen, C; Barker, G; Barr, G; Bentham, S; Bertram, I; Boyd, S; Briggs, K; Calland, R; Carroll, J; Cartwright, S; et al. (2013)
The T2K experiment studies oscillations of an off-axis muon neutrino beam between the J-PARC accelerator complex and the Super-Kamiokande detector. Special emphasis is placed on measuring the mixing angle theta_13 by observing electron neutrino appearance via the sub-dominant muon neutrino to electron neutrino oscillation, and searching for CP violation in the lepton sector. The experiment includes a sophisticated, off-axis, near detector, the ND280, situated 280 m downstream of the neutrino production target in order to measure the properties of the neutrino beam and to understand better neutrino interactions at the energy scale below a few GeV. The data collected with the ND280 are used to study charged- and neutral-current neutrino interaction rates and kinematics prior to oscillation, in order to reduce uncertainties in the oscillation measurements by the far detector. A key element of the near detector is the ND280 electromagnetic calorimeter (ECal), consisting of active scintillator bars sandwiched between lead sheets and read outwith multi-pixel photon counters (MPPCs). The ECal is vital to the reconstruction of neutral particles, and the identification of charged particle species. The ECal surrounds the Pi-0 detector (P0D) and the tracking region of the ND280, and is enclosed in the former UA1/NOMAD dipole magnet. This paper describes the design, construction and assembly of the ECal, as well as the materials from which it is composed. The electronic and data acquisition (DAQ) systems are discussed, and performance of the ECal modules, as deduced from measurements with particle beams, cosmic rays, the calibration system, and T2K data, is described.